Geomorphological significance of shelf-incised valleys as mesophotic habitats - Oliveira, Natacha de; Lavagnino, Ana Carolina; Rocha, Gabriela Aleixo; Moura, Rodrigo Leão de; Bastos, Alex Cardoso (Frontiers in Remote Sensing, 2023)
Geomorphology provides the core attributes for outlining marine seascapes, once the structural complexity of the seafloor mediates several oceanographic processes and ecosystem services, and is positively associated with biodiversity. Shelf-incised valleys and other prominent meso-scale structures such as reefs and sinkholes have a great potential for the discrimination of benthic habitat groups. Here, we investigate shelf-incised valleys as a mesophotic habitat, by focusing on their geomorphological control in forming distinct habitats in comparison with the flat surrounding area. The study was based on the integration of high-resolution bathymetry data (multibeam echosounder), video imaging, and physical-chemical parameters of the water column. Habitat mapping was conducted using object-based image analysis segmentation and clustering. Principal Component Analysis was used to assess the variables associated with habitat distribution at each morphological region of the valleys. Bathymetric data revealed the presence of 5 shelf-incised valleys and 5 seabed classes were defined as carbonate crusts, Rhodoliths (3 distinct classes) and unconsolidated sediments. A comprehensive habitat map with 17 classes was produced, and 13 are associated with valley´s relief. Extensive rhodolith beds were mapped in the valley flanks/bottom and in the flat areas. Shelf-incised valleys are prominent morphological features that add complexity to the seascape, contrasting with the flat relief that dominates the seascape. The seabed footage obtained in the valleys revealed that their heterogeneous, complex and irregular topography harbors a great diversity of epibionts, such as scleractinian corals, coralline algae, sponges and bryozoans. Most of the variability in the dataset is correlated with salinity, temperature and carbonate sediments, which seem to be the most influential variables over the biological assemblage, together with water depth and seabed slope. Shelf-incised valleys, similarly to submarine canyons, can define a complex mesophotic habitat and sustain distinct biodiversity, and even form mesophotic reefs. These features are the legacy of Quaternary sea-level changes and should be further investigated as important mesophotic habitats.